Tradition of Hileyiya: The Interaction Between Religion and Traditions in Gorontalo in Sociology of Islamic Law Perspective - Rizal Darwis (Analisa: Journal of Social Science and Religion, 2015)
Interaction between tradition and religion in Indonesia cannot be denied. Historically, the development of national law was based on three difference laws: customary law, western law (particularly Dutch law), and Islamic law. This affects on the acceptance of the tradition that does not contradict with the religious law.  This paper examines the tradition of hileyiya or funeral ceremony which is prominent among Gorontalo’s society from the sociology of Islamic law perspective. It is a descriptive qualitative research and the data was collected using observation, interviews, and document review. Finding of this study revealed that tradition of hileyiya consisting of the reciting of the Qur’an, tahlil, tahmid, shalawat and dzikir has become a legacy for Gorontalo’s society. In the sociology of Islamic law perspective, this practice provides various benefits to the dead family and the visitors. For instance, the benefits of reciting the Qur’an believed can be passed on to the dead, serve to tranquil the dead family, and remind people about the death. It can be regarded as al-urf-shahih (and it was legitimized by the basis of Islamic law as al-adat al-muhakkamah (customs can be law).